EDUKASI PEMANFAATAN SEREH MENJADI SPRAY DAN BODY LOTION SEBAGAI UPAYA MENURUNKAN KASUS DBD DI DUSUN BIRING JENE KAB MAROS - Yuliati; Andi Adillah Firstania Azis; Idhar Dharlis; Alfina Baharuddin (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract There were 50 cases of dengue fever in Biring Jene hamlet (35.5%). Based on the results of examinations for Aedes aegypti larvae, 12% of containers were positive for Aedes aegypti larvae in the house and 88% were negative. Meanwhile, the number of containers that were positive for Aedes aegypti larvae outside the home was 3% and those that were negative were 97%. House Index (HI)=27.6, Container Index (CI)=8.3, and Breteau Index (BI)=29.7. The aim of this service is: Reducing cases of dengue fever, increasing partner education through the use of natural ingredients such as lemongrass as a herbal ingredient in preventing dengue fever. The solution offered in this service activity is: education to partners regarding the application of natural, environmentally friendly ingredients as an effort to prevent dengue fever, namely lemongrass as lotion and spray. The results of the service showed that there was an increase in the partners' knowledge from the pre-test activities in the sufficient category (52.3%) while for the post-test it increased to 80%. There was an increase in the partners' attitudes from the pre-test activities in the sufficient category (60%) while for the post-test it increased to 83%. There was an increase in the actions of RT mothers from the pre-test activities in the sufficient category (55.0%) while for the post-test it increased to 80% Keywords: DHF, Lemongrass, Spray, lotion. Abstrak Kasus DBD di dusun biring jene terdapat 50 Kasus (35,5%). Berdasarkan hasil pemeriksaan jentik Aedes aegypti bahwa kontainer yang positif jentik Aedes aegypti di dalam rumah yaitu 12% dan yang negatif 88%. Sedangkan jumlah kontainer yang positif jentik Aedes aegypti di luar rumah yaitu 3% dan yang negatif 97%. House Index (HI)=27,6, Container Index (CI)=8,3, dan Breteau Index (BI)=29,7. Tujuan pengabdian ini adalah: Menurunan kasus DBD, Peningkatan edukasi mitra melalui pemanfaatan bahan alami sereh sebagai bahan herbal dalam pencegahan DBD. Solusi yang ditawarkan dalam kegiatan pengabdian ini adalah : edukasi kepada mitra terkait penerapan bahan alami yang ramah lingkungan sebagai upaya penceghaan DBD yaitu sereh menjadi lotion dan spray. Hasil pengabdian menunjukkan Terjadi peningkatan pengetahuan para mitra dari kegiatan pre test kategori cukup (52,3%) sedangkan untuk post test meningkat menjadi 80 %. Terjadi peningkatan sikap para mitra dari kegiatan pre test kategori cukup (60 %) sedangkan untuk post test meningkat menjadi 83%. Terjadi peningkatan tindakan para ibu-ibu RT dari kegiatan pre test kategori cukup (55,0%) sedangkan untuk post test meningkat menjadi 80% Keywords: DBD, Sereh, Spray, lotion.